A core@double shell-structured PBO composite with excellent dielectric properties and high heat resistance. Issue 18 (16th April 2019) - Liu, Qiang; Cheng, Zhipeng; Qian, Jun; Chen, Xuexue; Zhang, Yitong; Zhuang, Qixin
Abstract : Herein, a new high dielectric performance composite was prepared, which contained a core@double shell structure filler. Abstract : Herein, a new high dielectric performance composite was prepared, which contained a core@double shell structure filler. The fillers consisted of an Fe3 O4 core, a carbon (C) inner shell and a PANI outer shell. This core@double shell structure contributed to the homogeneous dispersion of fillers. Under the influence of an external electric field, a huge number of dipoles appeared in the region near the interfaces, which deeply influenced the dielectric behavior of the composite. At 1 kHz and room temperature, the Fe3 O4 @C@PANI/PBO composite retained a high dielectric constant (164), an ultralow dielectric loss (0.047) and a high breakdown strength (195.2 ± 9.5 kV mm −1 ). In addition, we inserted a PANI shell between the inorganic C shell and the organic matrix; this increased the compatibility of the fillers and endowed the nanocomposite with a high tensile strength (at 103 MPa) and tensile modulus (at 7.1 GPa). To achieve high thermal stability (at 670 °C), we synthesized poly- p -phenylene benzobisoxazole (PBO) and used it as a matrix. This new structure composite retained excellent comprehensive performance and could be used as an electronic component in a high temperature, corrosive, and huge mechanical strength working environment.